Updated distribution of Osmoderma eremita in Abruzzo (Italy) and agro-pastoral practices affecting its conservation (Coleoptera: Scarabaeidae) - Giangregorio, Patrizia; Audisio, Paolo; Carpaneto, Giuseppe Maria; Marcantonio, Giuseppe; Maurizi, Emanuela; Mosconi, Fabio; Campanaro, Alessandro (Fragmenta entomologica, 2015)
New records of Osmoderma eremita (Scopoli, 1763) (Coleoptera: Scarabaeidae: Cetoniinae) are reported for Abruzzo (Italy), together with a review of its distribution in this region. O. eremita is a saproxylic beetle dependent on the presence of hollow deciduous trees with abundant wood mould in their cavities. The major threats for the species are habitat loss and fragmentation. EU Habitats Directive requests to the member States its protection and the monitoring of its conservation status. Detection of its occurrence is the first step to protect the species. The surveys have been carried out in ten sites of Abruzzo by using black cross-windows traps baited with specific pheromone. The species has been recorded for the first time in the Sant’Antonio forest and its presence is confirmed in the Peligna Valley, after a decade. The populations seem to be confined to small patches of suitable habitats. At local level, the abandonment of the pollarding practice (willow and beech forests) and the use of pollarded trees as biomass for fuel are the major threats for this species. Indeed some key actions, such as the protection of old hollow trees and the continuation of pollarding practice in rural landscape, could be key factors for the conservation strategies of the species in the study area.